Condicionamento neotectônico na rede de drenagem da bacia hidrográfica do Rio Bananal - Espírito Santo - Brasil - Posses, Simoni Pereira das (2020)
This research has as main objective to investigate the neotectonic control in the drainage network in the hydrographic basin of the Bananal river, located in the North region of the state of Espírito Santo - Southeast of Brazil. The methodological basis used includes the analysis of the office and field. In the office, a bibliographic review, analyzes of the drainage network at a scale of 1: 100,000 (elaboration of drainage anomalies, drainage pattern, orientation of the drainage network, watershed asymmetry), lineament analysis, geomorphological analyzes ( hypsometric map, base surface map, scan profile) and neotectonic analysis of pre-existing data. All maps were created using the ArcGIS 10.1 ™ software (ESRI, 2012). In the field, the main drainage anomalies, lithologies of the geological compartments, aspects of the relief, and outcrops with data from neotectonic faults were identified and recorded. Based on the analysis of the lineaments, the drainage network, the relief and the neotectonics in the stages of the cabinet and field, it was possible to identify several physiographic elements that show neotectonic controls, which can be highlighted, particularly: a drainage network where the river channels geometrically organized, oriented lake, drainage anomalies, tectonically controlled drainage patterns, identification of tectonic blocks through the analysis of the base surface map and the scanning profile. In addition, some morphotectonic features, such as fault escarpment and morphotectonic / morphostructural (knickpoint) features, were identified during fieldwork. It was observed that the NNW-SSE and NW-SE guidelines of the lineaments, the guidelines of the drainage network and the orientations of the structural trends predominate in the Precambrian Basement and Sedimentary Deposit compartments. The NNE-SSW and NE-SW orientations are secondarily important in the two geological compartments of the basin. However, in the Cenozoic Sedimentary Deposit Compartment, these guidelines can be directly attributed to Neotectonic billing standards. In addition, there was a continuity of structural trends, present in the density map of lineaments that extend from sedimentary rocks to basement rocks, with the same orientation, being able to document neotectonic reactivations. The guidelines for the lineaments, structural trends and drainage network of the studied basin are the same as for the neotectonic failures present in the neotectonic regimes recognized for the state of Espírito Santo: i) sinister occurrence E-W, attributed to a neogenic age; ii) dextral occurrence E-W, considered to be of Pleistocene to Holocene age; and iii) NW-SE distension, of Holocene age, also recognized in other studies in southeastern Brazi